(untitled) (Proceedings OPTIMAL, 2024)
Anemia is one of the most common public health problems worldwide, particularly affecting women of childbearing age (brides-to-be) who will later give birth to future generations. Factors associated with anemia include iron tablet intake, nutritional status, the menstrual cycle, eating habits, and knowledge. The consequences of anemia include an increased risk of chronic energy deficiency (CED), inhibited fetal growth (IFG), premature birth, low birth weight (LBW), and developmental disorders in children. This study aimed to determine the determinants of anemia among prospective brides in the working area of UPTD Puskesmas Batoh , Lueng Bata District, Banda Aceh City. An analytical survey method with a cross-sectional design was used. The sample consisted of 56 brides-to-be, selected through total sampling. Data analysis involved univariate and bivariate analyzes using the Chi-square test. The univariate results showed that, among the 56 respondents, most did not have anemia (63.3%), consumed iron tablets (53.3%), had normal nutritional status (46.7%), regular menstrual cycles (60%), good eating habits ( 62%), and good knowledge (56.7%). The bivariate analysis revealed significant relationships between anemia and iron tablet consumption (p = 0.003), nutritional status (p = 0.009), menstrual cycle (p = 0.001), eating habits (p = 0.001), and knowledge (p = 0.002) in prospective brides. The study concluded that there were significant relationships between these factors and anemia.